Differentiating the pre-hydrolysis states of wild-type and A59G mutant HRas: An insight through MD simulations. (August 2017) - Sharma, Neeru; Sonavane, Uddhavesh; Joshi, Rajendra
Graphical abstract: Highlights: ∼15 μs of classical MD and 500 ns of metadynamics simulations to explore the dynamics of mutant A59G-Ras Role of "two water model" in hydrolysis of Ras protein complexes. Effect of A59G mutant on crucial Gln61 residue, Sw II region and DXXGQ motif. Incapability of capturing the pre-hydrolysis state by the oncogenic A59G mutant. Abstract: The most representative member of the Ras subfamily is its HRas isoform. Ras proteins being GTPases, possess an intrinsic activity to hydrolyze the GTP molecule to GDP. During the transition phases, between active and inactive states, P-loop and switch regions show maximum variations. Various hot-spot Ras mutants (G12 V, A59G, Q61L etc) have been reported, that limit the protein's conformation in the permanent active state. In the present study, we aim to explore the structural dynamics of one such crucial mutant of Ras namely A59G which belongs to the conserved Switch II region of the protein. Approximately ∼15 μs of Classical Molecular Dynamics (CMD) simulations have been carried out on the mutant and wild-type complexes. Further, a metadynamics simulation of 500 ns was also carried out, which suggests an energy barrier of ∼9.56 kcal/mol between wild-type and mutant conformation. We demonstrate the role of water molecule in maintaining the required interaction networks in the pre-hydrolysis state, its impact on A59G mutation, distinct orientation of the Gln61 residue in two conformations, disruption of crucial Gly60 and γ phosphate and the change in the Switch II region. The outcome of our study captures the pre-hydrolysis state of the HRas protein. It also establishes the fact that this mutation makes the movement of Switch II region and the conserved DXXGQ motif highly constrained, which is known to be an important requirement for hydrolysis. This suggests that the A59G mutation may decrease the rate of intrinsic hydrolysis as well as GAP-mediated hydrolysis.